Marketing Communication Strategies and Packaging Innovation of Thai Desserts - Bilmanoch, Sasiphan; Chonphithak, Bancha (Siam Communication Review, 2022)
This article presents about packaging innovation that helps promote the identity of Thai desserts. Currently, the characteristics of Thai desserts have been modified to be more modern, beautiful, and more appetizing. Including the packaging of Thai desserts, it is an important factor that entrepreneurs have applied marketing communication strategies in their packaging design. As packaging can have an effect in attracting consumers to be interested and make purchasing decisions. Packaging is therefore a factor that helps promote marketing strategies. In order to help increase sales for each product also it creates more value and can build trust and acceptance of consumers as well.